2020
DOI: 10.1093/cid/ciaa1071
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Outbreak in a San Francisco Homeless Shelter

Abstract: We report the public health response to a COVID-19 outbreak in a San Francisco shelter where 67% of residents and 17% of staff tested positive for SARS-CoV-2. We describe the limited utility of case investigation, person-based contact tracing and symptom screening, and the benefits of mass testing in outbreak response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 6 publications
0
94
4
Order By: Relevance
“…Eight of the cross-sectional quantitative studies were conducted in the USA [18][19][20][21][22][23][24][25] , one in Canada 26 and one in France 27 . All studies collected data from March to early May 2020 during the first wave of the SARS-Cov-2 pandemic, except one 20 , conducted from April to August 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the cross-sectional quantitative studies were conducted in the USA [18][19][20][21][22][23][24][25] , one in Canada 26 and one in France 27 . All studies collected data from March to early May 2020 during the first wave of the SARS-Cov-2 pandemic, except one 20 , conducted from April to August 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Also, homeless persons have more physical and mental comorbidities, usually undiagnosed and uncontrolled, that may worsen the disease's course. In these congregated living settings, asymptomatic cases represent the most common means of contagion, as reported by Baggett in Boston ( Baggett et al, 2020 ), Tobolowsky in Seattle and King County ( Tobolowsky et al, 2020 ), and Imbert in San Francisco ( Imbert et al, 2020 ) ( Table 1 ).…”
mentioning
confidence: 87%
“…For instance, Arcadepani et al (2020) highlight the challenges of COVID-19 prevention in public and open-air drug scenes, focusing on a case study in São Paulo, Brazil. A particular challenge is delivering COVID-19 prevention and quarantine services to homeless populations ( Banerjee and Bhattacharya, 2020 , Lenhard, 2020 , Marcus et al, 2020 ), particularly in settings where outbreaks have been observed ( Baggett et al, 2020 , Imbert et al, 2020 , Mosites et al, 2020 , Tobolowsky et al, 2020 ). This special issue highlights some of the specific challenges in providing COVID-19 prevention services among homeless people who use drugs in Iran ( Deilamizade & Moghanibashi-Mansourieh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%